Miscellaneous Morphological Problems in Indo-European Languages (I-II) - Rasmussen, Jens Elmegård
1. Hittite memai, memijanzi "speak(s)", S. 27-31; 3. Old Irish olsé "said he", Lat. uls, and the Hittite Ablative, S. 34-37.